Genomic Characterization of Flavobacterium psychrophilum Serotypes and Development of a Multiplex PCR-Based Serotyping Scheme - Rochat, Tatiana; Fujiwara-Nagata, Erina; Calvez, Ségolène; Dalsgaard, Inger; Madsen, Lone; Calteau, Alexandra; Lunazzi, Aurélie; Nicolas, Pierre; Wiklund, Tom; Bernardet, Jean-François; Duchaud, Eric (Frontiers in Microbiology, 2017)
Flavobacterium psychrophilum is a devastating bacterial pathogen of salmonids reared in freshwater worldwide. So far, serological diversity between isolates has been described but the underlying molecular factors remain unknown. By combining complete genome sequence analysis and the serotyping method proposed by Lorenzen & Olesen (1997) for a set of 34 strains, we identified key molecular determinants of the serotypes. This knowledge allowed us to develop a robust multiplex PCR-based serotyping scheme, which was applied to 244 bacterial isolates. The results revealed a striking association between PCR-serotype and fish host species and illustrate the use of this approach as a simple and cost-effective method for the determination of F. psychrophilum serogroups. PCR-based serotyping could be a useful tool in a range of applications such as disease surveillance, selection of salmonids for bacterial coldwater disease resistance and future vaccine formulation.